Intrafamily violence against the elderly: Systematic review - de Medeiros Pinheiro Cachina, Alanna (2016)
This systematic review of the literature was carried out on a national journals basis, between June / 2015 and February / 2016, using the descriptors: «intrafamily violence and elderly» and «mistreatment and elderly», in order to identify the frequencies of the studies, years of publications, major difficulties of the network and how the problem of violence is perceived by the study participants. In this sense, the objective was to characterize the studies about domestic violence against the elderly, identifying difficulties and forms of confrontation found by the network of protection to the elderly victims of violence. In the method, it was used as selection criteria: papers that address with the issue of intrafamily violence against the elderly, non-duplicity and national publications. A total of 17 differentpapers were identified, published between 2007 and 2014. The results showed as main difficulties in dealing with the problem of intrafamily violence against the elderly: underreporting, absence of flow between components of the protection network, lack of preparation of health teams to deal with the problem and deficit in the structure to work with this demand. Regarding the recurrent forms of confrontations, the most indicated strategies were articulation between services for the protection of the elderly, strengthening support for the elderly and their families, investment in the training of health professionals, and actions directed to the attention of thecaretaker.